Not business as usual: Engaging the corporate sector in India's TB elimination efforts - Madeline Carwile; Chelsie Cintron; Komal Jain; Giancarlo Buonomo; Matt Oliver; Madolyn Dauphinais; Prakash Babu Narasimhan; Senbagavalli Prakash Babu; Sonali Sarkar; Lindsey Locks; Nalin Kulatilaka; Natasha Hochberg; et al. (Taylor & Francis Group, 2023)
India has the highest global burden of tuberculosis (TB), accounting for a quarter of the worldwide TB disease incidence. Given the magnitude of India's epidemic, TB has enormous economic implications. Indeed, the majority of individuals with TB disease are in their prime years of economic productivity. Absenteeism and employee turnover due to TB have economic ramifications for employers. Furthermore, TB can easily spread in the workplace and compound the economic impact. Employers who fund workplace, community, or national TB initiatives stand to gain directly and also enjoy reputational benefits, which are important in the era of socially conscious investing. Corporate social responsibility laws in India and tax incentives can be leveraged to bring the logistical networks, reach, and innovative spirit of the private sector to bear on India's formidable TB epidemic. In this perspective piece, we explore the economic impacts of TB; opportunities for and benefits from businesses contributing to TB elimination efforts; and strategies to enlist India's corporate sector in the fight against TB.